Role conflict and changing heritage practice: ancestral tourism in Scotland. Issue 15 (12th October 2016) - Murdy, Samantha; Alexander, Matthew; Bryce, Derek
ABSTRACT: Developing mutually beneficial outcomes in service encounters can be challenging due to resource asymmetry within co-created experiences. Such encounters can result in role conflict for service providers. Limited attention has been paid to the effect on service providers of highly collaborative exchanges which require specific customisation. An example of this is ancestral tourism, a dimension of heritage consumption, in which visitors actively participate in the co-creation of experience at museums, archives and related heritage sites. These institutions, previously seen as repositories of historical information, now act as conduits for visitors to investigate their ancestral past. The purpose of this study is to explore the relationship between changing professional discourse in the cultural heritage sector, specifically ancestral tourism, and role conflict amongst staff. Through interviews conducted with professionals, the extent and outcomes of role conflict in complex and collaborative exchanges are explored.